Hot thespian action! : ten premiere plays from Walterdale Playhouse - Whittaker, Robin, 1976- (Canadian plays series., 2008)
In Hot Thespian Action! Robin Whittaker argues that new plays can thrive in amateur theatres, which have freedoms unavailable to professionalized companies. And he proves it with 10 relevant, engaging playscripts originally produced by one of Canada's longest-running theatres, Edmonton's acclaimed Walterdale Theatre Associates. This collection challenges notions that amateur theatre is solely a phenomenon of the pre-professional past. Whittaker makes an important contribution to Canadian theatre studies with the first North American anthology in 80 years to collect plays first produced by a no.